Accelerated long-term aging study of new antioxidant plastic scintillators. (1st January 2023) - Song, H.; Li, X.; Yu, B.; Yang, C.; Ling, X.; Zhu, Z.; Hu, T.; Zhao, T.; Jin, B.; Zhang, H.
Abstract: In this paper, the smaller plastic scintillator (polystyrene as solvent) tiles are polymerized and shaped by two methods, i.e. injection molding technology and thermal pressing technology by domestic manufacturer, to be operated for more than 10 years in the hadron calorimeter of the Circular Electron Position Collider (CEPC) or other purposes. Other benefits include, researching aging problems, by adding 0.1% material antioxidants of 2, 6-Di-tert-butyl-4-methylphenol (BHT) and without BHT, and according to Van't Hoff rule of equivalent chemical reaction rate of high temperature, the 10 years aging study is simulated in short term. A strobed coincidence setup is arranged to test the light yield of the tile to be measured with silicon photomultipliers (SiPMs) with ADC read out and a simple trigger system with small solid angle acceptance is adopted. The light yields of measured tiles without BHT decrease by about 26.6% (injection molding technology) and 43.3% (thermal polymerization technology) after ten-year equivalent aging time. Meanwhile, the light yields of the tiles with BHT almost did not change after ten-year equivalent aging time.